Effectiveness and Safety of Acupuncture to Treat Sleep Difficulties in Women on Hormone Replacement Therapy for the Treatment of Breast Cancer: A Randomized Controlled Trial. Issue 9 (25th September 2022) - E., E.; Jacoangeli, Jacoangeli; F., F.; Sebastiani, Sebastiani; C., C.; Scoppola, Scoppola; A., A.; Cerutti, Cerutti; M., M.; Castellucci, Castellucci; P., P.; Menichelli, Menichelli; et al.
No abstract available